(3JUeje hJfSjb GdMOGFb GdNGUI (B/ s - (3GfLi eMeO SGeM ceGd GdOjf SGeM s; (3eMeO eMeO GdHQedLi (B: s ((3GdbGgQI (B: s (3GfLi eMeO SGeM ceGd GdOjf SGeM (B: s, 2015)
(3jJfGhd GdHMK JfSjb GdMOjbg GdefRdjg GdNGUg GdJi GfJTQJ HcKQg ai GdeOf GdLOjOg hGjVG GdefJLYGJ GdScfjg HGdSGMd GdTeGdi hcGf ef Gdege hVY GSS heYGjjQ dJUeje gPg GdMOGFb JSGYO GdegfOS GdeUee dJMbjb GdZQV GdeWdhH efgG h Pdc HCSdhH Ydei jaQV Ydjg GdbjGe HYed GdYOjO ef GdOQGSGJ ShGA cGfJ NGUg HGdfGMjg GdfHGJjg hGdJTLjQ Gh GdfGMjg GdGfTGFjg dcGag echfGJ GdMOjbg h jJchf GdHMK ef NeSg GHhGH h GQHYg YTQaUdG JMJhi Ydi JYQja GdMOjbg GdNGUg h OQGSg JWhQgG ai YUhQ eNJdag h JMdjd cGag GdHjGfGJ h GdeYdheGJ h QUOgG ai LOGhd h JWHjb Pdc GdGSdhH Ydi GMOi GdMOGFb hhVY feGPL eNJdag ddYOjO ef GdMOGFb GdNGUg GdJi UeeJ HGSdhH Ydeis
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdgfOSI (B- (3bSe GdgfOSI GdeYeGQjIs
(3UOQ GjVG cbQU eOeLs
Keywords: (3GdGSdhH GdYdei s; (3JfSjb GdMOGFb s; (3eYGjjQ GdJUeje s